The effects of smoking on pregnancy risks in women with polycystic ovary syndrome: a population-based study. Issue 9 (24th June 2021) - Feferkorn, I; Badeghiesh, A; Mills, G; Baghlaf, H; Dahan, M
Abstract: STUDY QUESTION: Is there is an association between smoking and pregnancy complications in pregnant women with polycystic ovarian syndrome (PCOS)? SUMMARY ANSWER: There is an increased risk of developing gestational diabetes mellitus (GDM) among women with PCOS who smoke. WHAT IS KNOWN ALREADY: Smokers are at increased risk of developing Type 2 Diabetes Mellitus (DM). Given the common pathophysiology and shared risk factors between type 2 DM and GDM, we sought to assess whether an association between smoking and the development of GDM exists. STUDY DESIGN, SIZE, DURATION: This is a retrospective population-based study utilizing data from the HCUP-NIS over 11 years from 2004 to 2014. Pregnant women with PCOS who did smoke were compared to pregnant women with PCOS who did not smoke. A second comparison was made between pregnant smokers with and without PCOS. Of the 443 590 women who smoked during pregnancy and the 14 882 women with PCOS, 631 women were both smokers and diagnosed with PCOS. PARTICIPANTS/MATERIALS, SETTING, METHODS: The Healthcare Cost and Utilization Project—Nationwide Inpatient Sample (HCUP-NIS) is the largest inpatient sample database in the USA and is composed of hospital inpatient stays submitted by hospitals throughout the entire country. Each year, the database provides information relating to 7 million inpatient stays, including patient characteristics, diagnosis and procedures. The data are representative of ∼20% of admissions to US hospitals across 48 states and the District of Columbia. MAIN RESULTS AND THE ROLE OF CHANCE: There were no differences in the risks of preterm delivery (aOR1.2; CI 0.8–1.9), placental abruption (aOR1.1; CI 0.4–3.2), pregnancy induced hypertension (aOR1.0; CI 0.7–1.5), rate of operative vaginal delivery (aOR1.5; CI 0.9–2.5) and rates of cesarean section (C/S) (aOR1.0; CI 0.7–1.3) between smoking and non-smoking women with PCOS. A significant association between smoking and GDM was observed in women with PCOS (aOR1.5; CI1.01–2.1). LIMITATIONS, REASONS FOR CAUTION: The limitations of our study are its retrospective nature and the fact that it relies on an administrative database. Data regarding smoking and PCOS diagnosis could be skewed due to patients' underreporting, lack of documentation and documentation differences. WIDER IMPLICATIONS OF THE FINDINGS: The public health implications of confirming smoking as a risk for GDM among women with PCOS are many. This can lead to earlier screening in pregnancy of smokers for GDM. Earlier initiation of interventions could decrease fetal complications and possibly have an impact on the life and long-term health of the offspring. Future studies are needed in order to assess whether smoking cessation during pregnancy decreases the risk of GDM in that gestation. STUDY FUNDING/COMPETING INTEREST(S): No external funding was used. The authors report no competing interests. TRIAL REGISTRATION NUMBER: N/A.